Zimbabwe : Third Review Under the Staff-Monitored Program and Successor Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Zimbabwe's Third Review Under the Staff-Monitored Program (SMP) and the successor SMP. Zimbabwe has succeeded in keeping macroeconomic conditions relatively stable, despite difficult political and economic circumstances. In particular, the precarious external position improved somewhat, with higher international reserves and a projected lower current account deficit in 2014. The SMP will cover a 15-month period, October 2014 through December 2015, and will be monitored based on quantitative targets and structural benchmarks. The IMF staff welcomes the authorities' intention to continue to seek financing through grants or loans that are as concessional as possible, and to limit contracting nonconcessional loans within the ceilings set under the program.